The First Occurrence of a Basal Tyrannosauroid in Southeast Asia: Dental Evidence from the Upper Jurassic of Northeastern Thailand - Chowchuvech, Wongwech; Manitkoon, Sita; Chanthasit, Phornphen; Ketwetsuriya, Chatchalerm (Tropical Natural History, 2024)
Isolated theropod teeth are one of the most common vertebrate fossils that have been found in the Khorat Group of Thailand. Furthermore, several isolated teeth have been discovered from the Upper Jurassic Phu Kradung Formation, located in Phu Noi locality of Kalasin Province, Northeastern Thailand. Three of those theropod teeth from the Phu Noi locality show unique dental features that can be distinguished from previous discovered metriacanthosaurid theropod, including the lateral teeth with mesiolingual twisted mesial carinae extending above the cervix line and braided enamel surface texture. Morphological examination with cladistics and morphometric analyses show that these isolated teeth exhibit the synapomorphies of basal tyrannosauroids, closely related to Guanlong wucaii and Proceratosaurus bradleyi from the Jurassic Period. This paper notes the first report of a basal tyrannosauroid in Southeast Asia as well as significantly contributes to our understanding of paleoecology of the Upper Jurassic Phu Kradung Formation and paleobiogeography of Tyrannosauroidea during the Jurassic Period.